Controlling the Molecular Rotational Wave Packet Accurately by Femtosecond Laser Pulses (Journal of Atomic and Molecular Sciences, 2021)
We investigate the rotational wave packet modified by femtosecond laser pulses. The calculations are performed by solving numerically the full time-dependent Schrödinger equation for the $N_2$ molecule at finite rotational temperature. It is demonstrated that the rotational wave packet induced by the first laser pulse can be controlled exactly just by selecting the optimal time at which the second laser pulse is introduced. Whether the pulse duration of the two lasers is equal or not, the molecular alignment induced by the first laser pulse can be enhanced or degraded by precisely inserting the peak of the second laser pulse at the maximum or minimum position of the slope curve for the alignment parameter by the first laser. Furthermore, the already enhanced alignment by the two lasers can be enhanced or degraded by precisely inserting the peak of the third laser at the maximum or minimum position of the slope curve for the alignment by the two lasers. The already degraded alignment by the two lasers can be increased again from the isotropic distributed ensemble by precisely inserting the peak of the third laser at the peak position of the slope curve by the two lasers.